Implementation Of Maqasid Al-Shariah Principles In National Economic Policy - Zumara, Zumara; Hidayat, Rafi Nur; Putri, Rivani Dwi Sivana (Doktoral Ilmu Manajemen, Universitas Pasundan, 2024)
This research aims to explore and analyze the implementation of Maqasid Al-Shariah principles in national economic policy. Maqasid Al-Shariah, which refers to the main goal of Islamic law, includes the protection of religion, soul, mind, lineage and property. In an economic context, these principles are implemented to achieve general welfare and social justice. This research uses a qualitative approach with literature study methods and analysis of relevant national economic policy documents. The research results show that the principles of Maqasid Al-Shariah have been integrated into several economic policies, such as financial inclusion, zakat and waqf policies. However, challenges remain in the effective and consistent implementation of these principles. This research suggests the need to increase institutional capacity, better supervision, and increase public awareness to ensure that the economic policies taken are truly in line with Maqasid Al-Shariah's objectives. In this way, it is hoped that a more just and sustainable economic system can be created in accordance with Islamic values.